The Multifaceted Role of Annexin A1 in Viral Infections - Filipe Resende; Simone de Araújo; Luciana Pádua Tavares; Mauro Martins Teixeira; Vivian Vasconcelos Costa (Cells, 2023)
Dysregulated inflammatory responses are often correlated with disease severity during viral infections. Annexin A1 (AnxA1) is an endogenous pro-resolving protein that timely regulates inflammation by activating signaling pathways that culminate with the termination of response, clearance of pathogen and restoration of tissue homeostasis. Harnessing the pro-resolution actions of AnxA1 holds promise as a therapeutic strategy to control the severity of the clinical presentation of viral infections. In contrast, AnxA1 signaling might also be hijacked by viruses to promote pathogen survival and replication. Therefore, the role of AnxA1 during viral infections is complex and dynamic. In this review, we provide an in-depth view of the role of AnxA1 during viral infections, from pre-clinical to clinical studies. In addition, this review discusses the therapeutic potential for AnxA1 and AnxA1 mimetics in treating viral infections.